2008
DOI: 10.1007/s00431-008-0887-7
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory stridor and dysphagia in two newborn infants caused by ectopic thymus tissue

Abstract: We report two cases of ectopic cervical thymus, a solid thymic lesion, and a thymus cyst causing inspiratory stridor and mild dysphagia in the neonatal period. Because of the rarity of thymic dystopia, the two masses were initially misdiagnosed as more common entities, namely, lymph node enlargement and lymphangioma, respectively. The correct diagnosis was made only after surgical excision and histopathological examination. This case report is completed by a short review of embryogenic development, diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The respiratory symptoms are induced by the lesion's compression of the cervical trachea [3,26,29]. Severe respiratory distress had developed in some serious cases [2][3][4][5]21], and mechanical asphyxia leading to death was reported in an additional instance [6]. Shackelford et al also reported a case, similar to our first case, presenting with tracheal compression and obstructive airway symptoms when the baby was placed in a prone position [39].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The respiratory symptoms are induced by the lesion's compression of the cervical trachea [3,26,29]. Severe respiratory distress had developed in some serious cases [2][3][4][5]21], and mechanical asphyxia leading to death was reported in an additional instance [6]. Shackelford et al also reported a case, similar to our first case, presenting with tracheal compression and obstructive airway symptoms when the baby was placed in a prone position [39].…”
Section: Discussionmentioning
confidence: 52%
“…Ectopic cervical thymus (ECT) is a rare congenital anomaly found in 1% of pediatric autopsies [1]. Most cases follow an indolent course, but several cases have shown life-threatening symptoms such as respiratory distress due to tracheal compression [2][3][4][5]. Only 1 fatal case, caused by mechanical asphyxia, has been previously reported [6].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal and histological examination is often the only way to prove the diagnosis (Cigliano et al 2009;Felgentreff et al 2009;Meyer et al 2010;Nasseri and Eftekhari 2010). The cystic version of aberrant thymic tissue is more abundant than the "classical" solid form.…”
Section: Cystic Accessory Thymic Tissuementioning
confidence: 99%
“…Ectopic cervical thymic tissue is a rare cause of neck masses in pediatric patients (2). It is usually asymptomatic, but may occasionally present with clinical symptoms such as dysphagia or stridor (3). This case illustrates the following educational points:…”
Section: Case Reportmentioning
confidence: 99%